Rotational and vibrational dynamics in the excited electronic state of deprotonated and protonated fluorescein studied by time-resolved photofragmentation in an ion trap - Dimitri Imanbaew; Maxim F. Gelin; Christoph Riehn (Structural Dynamics, 2016)
Excited state dynamics of deprotonated and protonated fluorescein were investigated by polarization dependent femtosecond time-resolved pump-probe photofragmentation in a 3D ion trap. Transients of deprotonated fluorescein exhibit vibrational wavepacket dynamics with weak polarization dependence. Transients of protonated fluorescein show only effects of molecular alignment and rotational dephasing. The time resolved rotational anisotropy of protonated fluorescein is simulated by the calculated orientational correlation function. The observed differences between deprotonated and protonated fluorescein are ascribed to their different higher lying electronically excited states and corresponding structures. This is partially supported by time-dependent density functional theory calculations of the excited state structures.